2022
DOI: 10.1002/chem.202202475
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Triggered Chemical Transformation of Perovskite Nanocrystals

Abstract: Recently emerged lead-halide perovskite nanocrystals (PNCs) are promising optoelectronic material due to their easy solution processability, wide range of color tunability, as well as very high photoluminescence quantum yield. Despite their significant success in lab-scale optoelectronic applications, the long-term stability becomes the main issue, hindering them towards commercialization. The highly ionic nature of such lead-halide structure makes them extremely unstable in water and air. But a very few group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The deterioration of halide perovskites when exposed to water is associated with hydration, phase transition, degradation, and dissolution 11,12 . In certain instances, however, small amounts of water have proven beneficial, aiding in regulating the crystallization process to achieve superior-quality perovskite films and enhanced device performance 13,14 . The challenge is exacerbated in the environment of aqueous solution: if a cuttingedge CH 3 NH 3 PbI 3 halide perovskite film is placed in contact with water, the corresponding optoelectronic conversion process deactivates instantaneously and the water-induced bleaching phenomenon occurs 15 .…”
Section: Data-driven Optimization and Machine Learning Analysis Of Co...mentioning
confidence: 99%
“…The deterioration of halide perovskites when exposed to water is associated with hydration, phase transition, degradation, and dissolution 11,12 . In certain instances, however, small amounts of water have proven beneficial, aiding in regulating the crystallization process to achieve superior-quality perovskite films and enhanced device performance 13,14 . The challenge is exacerbated in the environment of aqueous solution: if a cuttingedge CH 3 NH 3 PbI 3 halide perovskite film is placed in contact with water, the corresponding optoelectronic conversion process deactivates instantaneously and the water-induced bleaching phenomenon occurs 15 .…”
Section: Data-driven Optimization and Machine Learning Analysis Of Co...mentioning
confidence: 99%
“…Recently emerged lead halide perovskites exhibit exceptional optoelectronic properties, which results in their multidimensional uses in photovoltaics, light-emitting devices, photocatalysis, etc. Despite their outstanding optical properties, the soft and polar nature of the perovskite crystals imposes a severe limitation in their device application due to water and moisture instability. , Therefore, several researchers are engaged to design water-stable perovskites via polymer encapsulation, engineering with the A-site cation, etc. However, fewer groups took advantage of the polar nature of the perovskite crystals and used the water-triggered chemistry constructively to initiate new chemical transformation. , Zhang et al reported the first water-assisted chemical transformation strategy from nonluminescent zero-dimensional Cs 4 PbBr 6 nanocrystals (NCs) to strongly luminescent three-dimensional CsPbBr 3 NCs in hexane . Later on, the idea of water-triggered chemistry is extended by them and a few other groups to develop a variety of morphology and composition-controlled perovskite NCs. The water-triggered strategy has the advantage of providing a clean environment for the reaction to take place as water and hexane are immiscible solvents compared to those reported in the miscible polar–nonpolar solvents .…”
mentioning
confidence: 99%
“…8−10 However, fewer groups took advantage of the polar nature of the perovskite crystals and used the water-triggered chemistry constructively to initiate new chemical transformation. 11,12 Zhang et al reported the first water-assisted chemical transformation strategy from nonluminescent zero-dimensional Cs 4 PbBr 6 nanocrystals (NCs) to strongly luminescent threedimensional CsPbBr 3 NCs in hexane. 13 Later on, the idea of water-triggered chemistry is extended by them and a few other groups to develop a variety of morphology and compositioncontrolled perovskite NCs.…”
mentioning
confidence: 99%
“…To this end, various different approaches have been developed, ranging from direct synthesis methods to post-synthetic cation exchange reactions. , In particular, the post-synthetic approach is advantageous, where a Mn precursor is introduced to presynthesized perovskite NCs, and therefore the Mn precursor does not need to face any competition from the Pb precursor. Recent reports on the Mn doping at the water–hexane interface provide a clean post-synthetic approach where the Mn dopant comes from the aqueous phase via a shuttling ligand. , In fact, the water-triggered approach recently led to a plethora of post-synthetic chemical transformations of perovskite NCs using unique interfacial chemistry. Although many forms of CsPbCl 3 :Mn 2+ NCs have been developed, doping in excitonic perovskite quantum dots (QDs) remains elusive. While nanoplate thickness-dependent Mn doping has been achieved, , the size-dependent Mn doping and its influence on the optical properties in perovskite QDs are still missing.…”
mentioning
confidence: 99%